EVALUASI PROSES PEMBELAJARAN PAI DAN BUDI PEKERTI PADA MASA PEMBELAJARAN TATAP MUKA TERBATAS MENGGUNAKAN MODEL TYLER DI KELAS XI IPS DI SMAN 1 BENAI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI (TA.2021/2022) - Wirza Rahmasari; A. Mualif; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2023)
The background of this research is (1) Less than maximum, yes,the delivery of material or assignments by the teacher un the teaching and learning process. (2) Teachers cannot use learning methods or model’s due to time constraints. (3) Student do not accept or understand learning due to time constraints. This study aims to evaluate the Tyler model in the PAI and Budi Pekerti learning process during the limited face-to-face learning period in class XI IPS at SMA Negeri 1 Benai, Benai District, Kuantan Singingi Regency (FY 2021/2022). This research is a qualitative research, the population of this study are all students of SMA Negeri Benai, the sample in this study amounted to 41 people, namely students of class XI IPS 1 and XI IPS 2 and 1 teacher of PAI and Budi Pekerti, data collection was done by observation, interviews and documentation, as well as data analysis techniques using descriptive statistics. This research is a qualitative research, the population of this study are all students of SMA Negeri Benai, the sample in this study amounted to 41 people, namely students of class XI IPS 1 and XI IPS 2 and 1 teacher of PAI and Budi Pekerti, data collection was done by observation, interviews and documentation, as well as data analysis techniques using descriptive statistics. Based on the results of the study, it was found that the evaluation of the Tyler model, namely: Evaluation of the learning process of PAI and Budi Pekerti uses the Tyler model for class XI IPS at SMA Negeri 1 Benai during the face-to-face learning period, the material is limited to respect and obedience to parents and teachers. The learning objectives were con veyed well about 77% by the subject matter teachers, fairly well conveyed about 14% and less well conveyed about 8%. Evaluation of the learning process of PAI and Budi Pekerti uses the Tyler model for class XI IPS at SMA Negeri 1 Benai during the face-to-face learning period, the material is limited to respect and obedience to parents and teachers. Learning objectives were conveyed well about 50% by student, quite well conveyed about 33%, less well conveyed about 8% and could not be achieved at all or did not belong to any category around 9%